2021
DOI: 10.1186/s12888-021-03581-9
|View full text |Cite
|
Sign up to set email alerts
|

Parenting experiences of Chinese mothers living with a mental illness

Abstract: Background Although the experiences of mothers with mental illness are well researched in Western countries, little is known about the experiences of Chinese mothers. This study aims to explore the experiences of family life and parenting of Chinese mothers, in the context of their mental illness. Methods Fourteen Chinese mothers with mental illness undertook in-depth, semi-structured interviews. Interpretative Phenomenological Analysis was employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…The adverse impact of stigma on parents' sense connection to their authentic selves found within the current psychosis‐specific parenting sample extends findings from previous studies of mothers and fathers who experience SMI (e.g. Chen et al, 2021; Diaz‐Caneja & Johnston, 2004; Nicholson et al, 1998; Parrott et al, 2015; Savvidou et al, 2003). However, this study suggested that fathers experienced shame particularly profoundly, especially around their perceptions of their ability to ‘provide’.…”
Section: Discussionsupporting
confidence: 84%
“…The adverse impact of stigma on parents' sense connection to their authentic selves found within the current psychosis‐specific parenting sample extends findings from previous studies of mothers and fathers who experience SMI (e.g. Chen et al, 2021; Diaz‐Caneja & Johnston, 2004; Nicholson et al, 1998; Parrott et al, 2015; Savvidou et al, 2003). However, this study suggested that fathers experienced shame particularly profoundly, especially around their perceptions of their ability to ‘provide’.…”
Section: Discussionsupporting
confidence: 84%
“…In fact, the few existing studies on the lived experience of consumer-parents and their families in China suggested the very opposite. A pioneering study on the parenting experiences of Chinese mothers living with mental illness showed that Chinese mothers with mental illness were often worried about the impact of their mental illness on children, wanted to talk about children with mental health professionals, and emphasized the need of psycho-education for their families and children (Chen et al, 2021). Another study on the lived experience of COPMI in China also reported that these children were often faced with feelings of helplessness, worry and isolation and longed for professional support (Zhou, 2020).…”
Section: Worker Workplace and Client Factors In The Context Of Ffp Am...mentioning
confidence: 99%
“…Children whose parents have mental illnesses are victimised among their peers as a result of their association with parental mental illness. The affiliate stigma seems to come from public stigma towards people with mental illnesses, if they do not receive from proper sources the knowledge on mental illness (Chen et al, 2021; Reupert et al, 2021). Although peers may engage in such abusive behaviours due to their lack of understanding of mental illness, it has to do with broader societal views and attitudes that they have been socialised within.…”
Section: Resultsmentioning
confidence: 99%